A HISTORICAL STUDY ON THE CONTRIBUTION OF SALESIAN MISSIONARIES TO EDUCATION IN ASSAM - Narzary, Justin; Basumatary, Sudev Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Salesians of Don Bosco are well known for ‘Don Bosco’ educational institutions. Right from the very beginning of Salesian presence in Northeast India, “Don Bosco”, has been synonymous with good education. Don Bosco institutions have sought to impart quality education, relating the knowledge of science and technology, to knowledge of humanities, reinforcing it with the values of Don Bosco’s way of education as a source of meaning for life furthering the process of learning and building a society that transcends caste and creed. In Assam region of India, the work of the Salesians was greatly appreciated by the people in general as well as by government officials and others in responsible positions. The main educational centre’s set up by the Salesians in the bigger cities of the region attracted students from throughout the State of Assam and perceptibly helped further their economic and social development. The present paper, attempts to highlight some of the significant contribution of Salesian missionaries in the field of school education, technical education and infrastructural facilities in state of the Assam.